Role of two efflux proteins, ABCB1 and ABCG2 in blood-brain barrier transport of bromocriptine in a murine model of MPTP-induced dopaminergic degeneration - Milane, Aline (2009)
Purpose: MPTP-induced dopaminergic degeneration is an experimental model commonly used to explore Parkinson’s disease. Cerebral drug transport by ABC transporters in MPTP models has never been reported. Methods: We have investigated the transport of bromocriptine through the blood-brain barrier (BBB) in a MPTP model to understand the influence of the dopaminergic degeneration on ABCB1 and ABCG2. Results: We have shown that in MPTP treated mice, bromocriptine is widely distributed to brain (2.3-fold versus control, p<0.001) suggesting either disruption of BBB or alteration of active efflux of the drug. The investigation of BBB did not evidence a modification of permeability. Studies of ABCB1 and ABCG2 activity showed that MPTP intoxication did not alter their functionality. Conversely, ABCG2 expression studied on brain capillaries from MPTP-treated mice was decreased (1.3-fold, p<0.05) and ABCB1 expression increased (1.43-fold, p<0.05) as an off-setting of brain transport. Conclusions: These data demonstrate that MPTP intoxication does not alter BBB permeability. However, bromocriptine brain distribution is increased in MPTP animals. Hence, MPTP may interact with another transport mechanism such as uptake and/or other efflux transporters. Inflammation and Parkinson’s-like lesions induced by MPTP intoxication could lead to modification of drug pharmacokinetics and have clinical consequences, such as neurotoxicity.